Understanding the Causes of Roof Control Problems on a Longwall Face From Shield Monitoring Data ? A Case Study - Robert Trueman (International Conference on Ground Control in Mining, 2011)
This paper details the results of an assessment aimed at understanding the shield loading mechanisms associated with strata-related issues on a longwall face. Shield load cycle analysis theories developed by the authors were used to quantify the interaction between the shields and strata. Shield pressure data was back-analyzed using a version of the Longwall Visual Analysis (LVA) software that has been extended to enable efficient load cycle analysis to be undertaken. The software outputs enabled the shield strata interactions to be characterized. The results of the analyses indicated that the major cause of the roof falls was high-level periodic weighting, resulting in periodic shield overload. Exploration borehole data was analysed to identify and characterize the overburden unit that was the likely cause of the shield overloading.